A Study of Peripheral Lymphadenopathy with Correlation between Fine Needle Aspiration Cytology (FNAC) and Biopsy in A Tertiary Care Hospital (Bangladesh Journal of Medicine, 2015)
Background: Lymphadenopathy is a common clinical problem in our country among all age groups and in both sexes. In this study an attempt has been made to evaluate the clinical presentation and diagnosis of peripheral lymphadenopathy, which is commonly encountered in medical wards and diagnostic value of FNAC has been evaluated.Methodology: This hospital-based descriptive study was done in thirty adult cases, of clinically apparent peripheral lymphadenopathy of at least more than two weeks of duration. Study was conducted over a period of 6 months from July, 2005 to December, 2005 in inpatients and outpatients of Rajshahi Medical College Hospital. After thorough examination, fine needle aspiration from several accessible enlarged lymph node groups were taken and sent for cytopathological examination and later biopsy of the significantly enlarged lymph node from the same anatomical region was performed and was sent for histopathological examination.Results: Cytopathological study was successful in correctly identifying 84.6% of tubercular case, 85.7% of non-Hodgkins lymphoma, 66.7% of Hodgkins lymphoma, 83.3% of mitotic nodes and 100% of reactive nodes. Statistical correlation between aetiology of lymphadenopathy and cytopathological diagnosis with Spearmans rank correlation coefficient revealed a strong positive statistically significant correlation of cytopathology with aetiology, i.e. histopathology. Calculation of sensitivity, specificity, positive predictive value, negative predictive value, likelihood ratio for a positive test result and likelihood ratio for a negative test result confirms the diagnostic value of cytopathology in peripheral lymphadenopathy by demonstrating high values for different aetiology.Conclusion: The result of this study may not exactly reflect that of similar studies conducted home or abroad, probably due to smaller sample size and limited scope, but its strength remains in the fact that it attempted to address a widely prevalent condition in a practical way.Bangladesh J Medicine Jul 2015; 26 (2) : 49-54